Behind crimmigration : ICE, law enforcement, and resistance in America - Arriaga, Felicia (Book collections on Project MUSE., 2023)
"In recent years, dozens of counties in North Carolina have partnered with federal law enforcement in the criminalization of immigration-what many have dubbed 'crimmigration.' Southern border enforcement still monopolizes the national immigration debate, but immigration enforcement has become common within the United States as well. While Immigration and Customs Enforcement (ICE) operations are a major part of American immigration enforcement, Felicia Arriaga maintains that ICE relies on an already well-established system-the use of local law enforcement and local governments to identify, incarcerate, and deport undocumented immigrants"--